Measuring collaborative stakeholder influence and open budget actions - Welles Matias de Abreu; Ricardo Corrêa Gomes (Revista de Administração Pública, 2018)
Abstract Collaborative stakeholder influence and open budget actions are important elements in governance in order to promote social development (Ansell and Gash, 2008). However, it is important to clarify how to measure these supposedly independent elements. The aim of the article is to identify ways to measure the influence of collaborative stakeholders and open budget actions. The methodological aspects focus on data collection through interviews and content analysis. The conclusion is that the number of civil society organizations and the presence of social councils and their operational components are relevant measures of collaborative stakeholder influence and open budget actions, respectively. In addition, this article highlights the relevance of integrating collaborative stakeholder influences with open budget actions. Finally, a research agenda is proposed.